Multiscale Pedestrian Dynamics and Infection Spread Model for Policy Analysis - Namilae, Sirish; Derjany, Pierrot; Liu, Dahai; Mubayi, Anuj; Srinivasan, Ashok (Collective Dynamics, 2020)
In this paper, we present a formulation for a multiscale model combining a social force based pedestrian movement including collision avoidance and a stochastic infection dynamics framework to evaluate the spread of multiple infectious diseases during air travel. We apply the multiscale model to evaluate pedestrian movement strategies that can reduce infection spread during air travel. The results are presented for airport lounge and airplane boarding and deplaning. Use of parallel computing to evaluate the vast parameter space created due to stochasticity and discretionary pedestrian behavior is addressed.